Comparative evaluation of biodentine, resin-modified glass ionomer cement, cention-N, and bulk-fill flowable composite on fracture resistance in endodontically treated teeth: An in vitro study - Parthasarathi Mondal; Utpal Halder; Kaushik Mistry; Snigdho Das; Kallol Kumar Saha; Debjyoti Karmakar (Endodontology)
Aim: To assess the fracture resistance provided by four intraorifice barrier materials: biodentine (Septodont, Saint Maur des Fosses, France), resin-modified glass ionomer cement (RMGIC) (GC Gold label 2 LC Light Cured Universal Restorative, GC Products, Japan), cention-N (Ivoclar Vivadent, Schaan, Lichtenstein), and bulk-fill flowable composite (BFFC) (Shofu, Kyoto, Japan) in endodontically treated teeth. Methods: An in vitro comparative study, with a sample size of 50 freshly extracted mandibular second premolars. The teeth were randomly assigned into four experimental groups (n = 10 each) based on the type of intraorifice barrier applied: Group I (biodentine), Group II (RMGIC), Group III (cention-N), and Group IV (BFFC). A control group (n = 10) was included with no intraorifice barrier. Universal testing equipment (Instron, USA) was used to apply a compressive load to each specimen to evaluate its fracture resistance. Results: Group III exhibited the highest fracture resistance (906.27 ± 51.91 N), followed by Group IV (818.05 ± 57.93 N), Group I (684.73 ± 14.70 N), Group II (613.83 ± 59.30 N), and the control group (237.80 ± 18.87 N). Considerable differences were identified among the groups (P < 0.0001). Conclusion: Cention-N and BFFC provide superior fracture resistance compared to other tested materials.